Haptic Aesthetics and Bodily Properties of Ori Gersht’s Digital Art: A Behavioral and Eye-Tracking Study - Calbi, Marta; Aldouby, Hava; Gersht, Ori; Langiulli, Nunzio; Gallese, Vittorio; Umiltà, Maria Alessandra (Frontiers in Psychology, 2019)
Experimental aesthetics has shed light on the involvement of pre-motor areas in the perception of abstract art. However, the contribution of texture perception to aesthetic experience is still understudied. We hypothesized that digital screen-based art, despite its immateriality, might suggest potential sensorimotor stimulation. Original born-digital works of art were selected and manipulated by the artist himself. Five behavioral parameters: Beauty, Liking, Touch, Proximity, and Movement, were investigated under four experimental conditions: Resolution (high/low), and Magnitude (Entire image/detail). These were expected to modulate the quantity of material and textural information afforded by the image. While the Detail condition afforded less content-related information, our results show that it augmented the image’s haptic appeal. High Resolution improved the haptic and aesthetic properties of the images. Furthermore, aesthetic ratings positively correlated with sensorimotor ratings. Our results demonstrate a strict relation between the aesthetic and sensorimotor/haptic qualities of the images, empirically establishing a relationship between beholders’ bodily involvement and their aesthetic judgment of visual works of art. In addition, we found that beholders’ oculomotor behavior is selectively modulated by the perceptual manipulations being performed. The eye-tracking results indicate that the observation of the Entire, original images is the only condition in which the latency of the first fixation is shorter when participants gaze to the left side of the images. These results thus demonstrate the existence of a left-side bias during the observation of digital works of art, in particular, while participants are observing their original version.